The death of capital : how creative policy can restore stability - Lewitt, Michael E. (John Wiley & Sons, 2010)
A call for change that will create prolonged economic prosperity The Death of Capital discusses the phenomenon described as "the financialization of the U.S. economy" or how financial speculation came to dominate our economy at the expense of productive capital-resulting in an increasingly unstable economic base